2022
DOI: 10.1590/fst.73222
|View full text |Cite
|
Sign up to set email alerts
|

The effect of super-chilled preservation on shelf life and quality of beef during storage

Abstract: The effect of super-chilled storage (-2 °C) on shelf life and quality of beef was investigated, compared with chilled (4 °C) and frozen (-18 °C) storage. The pH value, color, TVB-N, water-holding capacity, total viable counts (TVC) and sensory evaluation were used to evaluate the freshness, shelf life and quality of beef. These results indicated that the fresh beef stored in super-chilled condition demonstrated better pH and color stability compared to chilled storage, and exhibited better water-holding capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Giselle et al applied chitosangelatin film to the retail preservation of steak, which significantly reduced the mass loss of steak and extended its shelf life [45]. TVB-N is the product of decomposition of protein by bacteria and enzymes in the process of spoilage of animal food and can be used to judge the freshness of meat [48]. Figure 9 shows the changes of TVB-N in beef during storage at 4 °C.…”
Section: Change In the Rate Of Mass Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Giselle et al applied chitosangelatin film to the retail preservation of steak, which significantly reduced the mass loss of steak and extended its shelf life [45]. TVB-N is the product of decomposition of protein by bacteria and enzymes in the process of spoilage of animal food and can be used to judge the freshness of meat [48]. Figure 9 shows the changes of TVB-N in beef during storage at 4 °C.…”
Section: Change In the Rate Of Mass Lossmentioning
confidence: 99%
“…It can be seen from the figure that with the extension of storage time, the content of TVB-N in all groups showed an increasing trend, and the content of TVB-N in the CK group increased faster. When stored to the sixth day, the TVB-N content of the CK group was 22.36 mg/100 g, and TVB-N is the product of decomposition of protein by bacteria and enzymes in the process of spoilage of animal food and can be used to judge the freshness of meat [48]. Figure 9 shows the changes of TVB-N in beef during storage at 4 • C. It can be seen from the figure that with the extension of storage time, the content of TVB-N in all groups showed an increasing trend, and the content of TVB-N in the CK group increased faster.…”
Section: Change In the Rate Of Mass Lossmentioning
confidence: 99%
“…The increased pH during storage was attributed to microbial metabolism. Due to microbial growth, the alkali compound release from muscular protein and nonprotein nitrogen-containing compounds was accelerated, thereby continuously accumulating alkali compounds (Binsi et al, 2014;Tian et al, 2022).…”
Section: Ph Of Crayfish Meat In the Storage Processmentioning
confidence: 99%
“…The storage temperature is closely related to the shelf life and quality of chicken nuggets with jack bean tempeh flour. Low temperatures can inhibit the growth and reproduction of microorganisms, reduce enzyme activity, and slow down various biochemical reactions in processed meat products such as chicken nuggets with jack bean tempeh flour substitution (Tian et al, 2022). Salama et al (2016) reported that cold storage plays a major role in extending the shelf-life of chicken nuggets in combination with vacuum packaging and coating of packaging material surface with rosemary or oregano extracts.…”
Section: Introductionmentioning
confidence: 99%